The putative maintaining mechanism of gut bacterial ecosystem in giant pandas and its potential application in conservation. (30th December 2022) - Cui, Xinyuan; Zhang, Qinrong; Zhang, Qunde; Chen, Hua; Liu, Guoqi; Zhu, Lifeng
Abstract: Animals living in captivity and the wild show differences in the internal structure of their gut microbiomes. Here, we performed a meta‐analysis of the microbial data of about 494 fecal samples obtained from giant pandas (captive and wild giant pandas). Our results show that the modular structures and topological features of the captive giant panda gut microbiome differ from those of the wild populations. The co‐occurrence network of wild giant pandas also contained more nodes and edges, indicating a higher complexity and stability compared to that of captive giant pandas. Keystone species analysis revealed the differences between geographically different wild populations, indicating the potential effect of geography on the internal modular structure. When combining all the giant panda samples for module analysis, we found that the abundant taxa (e.g., belonged to Flavobacterium, Herbaspirillum, and Escherichia‐Shigella ) usually acted as module hubs to stabilize the modular structure, while the rare taxa usually acted as connectors of different modules. We conclude that abundant and rare taxa play different roles in the gut bacterial ecosystem. The conservation of some key bacterial species is essential for promoting the development of the gut microbiome in pandas. The living environment of the giant pandas can influence the internal structure, topological features, and strength of interrelationships in the gut microbiome. This study provides new insights into the conservation and management of giant panda populations.